Tribo-mechanical properties of epoxy-cashew nut shell liquid-crumb rubber- friction dust-banana fiber composites. Issue 1 (1st January 2021) - Shivakumar, T.; Shivamurthy, B.; Thimmappa, B. H. S.; Mourad, Abdel-Hamid I.
Abstract: Epoxy-cashew nut shell liquid (E-CNSL) composites are prepared by open resin moulding method with varying CNSL content (16 to 30 vol. %.). The tensile properties, hardness and impact strength of E-CNSL composites were investigated as per ASTM standards. It is found that the addition of the CNSL in epoxy increases the elongation at break and tensile strength. The 16 vol. % CNSL addition showed maximum tensile strength, and further increased CNSL deteriorates the tensile properties of the resultant composites. Further, hybrid composites are prepared by reinforcing crumb rubber (CR), short banana fibre (BF) and friction dust (FD) in cashew nut shell liquid (CNSL) mixed epoxy. The samples were tested as per ASTM standards to investigate the basic mechanical properties. It is found that the hybrid composite made of 2.5 vol. % CR, 2.5 vol. % FD and 7.5 vol. % BF in epoxy with 16 vol. % of CNSL showed better properties. Further, the specific wear rate, coefficient of friction and rate of water intake is investigated for the hybrid composite and reported.